A pesquisa e o ensino desenvolvidos pelos licenciandos no estágio do curso de licenciatura em química da UEPG - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
This research has as general objective to recognize elements of research and analyze aspects that are part of teaching in articles produced by undergraduates in the internship of the Degree course in Chemistry of the State University of Ponta Grossa (UEPG). For this, we carried out a qualitative, exploratory and descriptive research in which, through content analysis, we identified research elements present in 71 final articles of the stage of the investigated course, and two aspects that are part of the teaching: the chemical content addressed and the didactic strategies adopted. The theoretical foundation of the dissertation is supported by authors who study the internship with research, research in Chemistry Teaching, the chemical contents worked in basic education and teaching methodologies and strategies. The analyses allowed establishing that the initial research interest of the undergraduates lies in "how to teach" and "what to teach". The theoretical basis of the research carried out by the undergraduates is adequate in some respect, whether in the methodology, in the theme adopted, in the didactic strategy, or in the three areas. The analyses of the methodologies described in the articles demonstrated a significant number of investigations that do not support their methodologies. The observation of the results presented by the undergraduates demonstrate that the research esum the theoretical foundation in the discussion, as well as discuss the data. In addition, the results of the research of the studies are linked to the student's learning, which suggests a mismatch between the interest of the undergraduates evidenced in focus 1 and the results obtained by them at the end of their research evidenced in focus 4. About the teaching developed by the graduates it was found that the most contemplated structuring content was synthetic chemistry and the least contemplated was biogeochemistry. The didactic strategies adopted mostly include strategies for the reproduction of reality, however, the greatest variety of strategies refer to those that seek to develop the protagonism and autonomy of the basic education student. Thus, this research can contribute to the improvement in the quality of research conducted at the stage of the investigated course and, consequently, in the training of chemistry teachers.
Keywords: Estágio Curricular Supervisionado; Licenciatura em Química; Estágio com pesquisa; Estratégias Didáticas; Conteúdo Químico; Supervised Curricular Internship; Degree in Chemistry; Internship with research; Didactic Strategies; Chemical Content; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA